Factors Affecting User Acceptance in Overuse of Smartphones in Mobile Health Services: An Empirical Study Testing a Modified Integrated Model in South Korea - Lee, Seo-Joon; Choi, Mun Joo; Rho, Mi Jung; Kim, Dai-Jin; Choi, In Young (Frontiers in Psychiatry, 2018)
Smartphones have become crucial to people’s everyday lives, including medical fields. However, as close as people are to smartphones, they are easily led to overuse. Problematic overuses lead to fatigue due to lack of sleep, depressive symptoms, social relationship failure, and in case of adolescents, hindered academic achievements. Self-control solutions are needed, but effective tools can be developed through behavioral analysis. Therefore, the aim of this study is to investigate the determinants of users’ intention to use m-Health for smartphone overuse interventions. Research model was based on TAM and UTAUT, which were modified to be applied to the case of smartphone overuse. Studied population included 400 randomly selected smartphone users from age 19 to age 60 in South Korea. Structural Equation Model (SEM) was conducted between variables to test hypothesis under 95% confidence interval. Perceived ease of use had a very strong direct positive association with perceived usefulness, and perceived usefulness had a very strong direct positive association with behavioral intention to use. Resistance to change had a direct positive association with behavioral intention to use, and lastly, social norm had a very strong direct positive association with behavioral intention to use. Findings regarding perceived ease of use influencing perceived usefulness, perceived usefulness influencing behavioral intention to use, and social norm influencing behavioral intentions to use were in accordance with prior related research. Other results that were not consistent with prior research implied unique behavioral findings regarding smartphone overuse. Research results are expected to provide critical factors to consider when implementing future systems or solutions that tackle the issue of smartphone overuse.